Kajian Teologis Pernikahan Poligami Menurut Perjanjian Lama dan Hukum Islam - Tulus Raharjo; Paulus Kunto Baskoro (JURNAL KADESI, 2023)
The social impact of polygamous marriage has colored the history of the growth and development of the human community on earth in general, the Indonesia people are inseparable. In Islam society it is believed the arrival of Islam. This writing focuses on the social impact, specifically the impact of social interaction that will be experienced for men and women who carry out polygamous marriages in Muslim societies and ancient Old Testament societies. The method ushed is descriptive literature method. The purpose of this paper is to examine theologically and empirically why polygamous marriages and not to lead a Sakinah (peacefull), mawadah (loving) and warahma (affection) from of marriage which is the main goal in Islamic marriages. The second objective is to examine why polygamous marriages have an impact on social relations for men and women who undergo polygamous marriages.